1) 10√3 - 4√48 -√75 = 10√3 - 4√(16*3) - √(25*3) =
= 10√3 - 4√(4² *3) - √ (5²*3) = 10√3 - 4*4√3 - 5√3 =
= 10√3 -16√3 -5√3= -11√3
2) √8р - √25 + √18р = √(2²*2р) - √5² + √(3²*2р) =
= 2√2р - 5 + 3√2р = 5√2р - 5
если нужно , то можно еще вынести общий множитель:
= 5(√2р -1)
3) √5 (3√5 +5√8) = 3√5 *√5 + 5√8 *√5 =
= 3*(√5)² + 5√(8*5) = 3 *5 + 5√40 =
= 15 + 5√(2²*10) = 15 + 5*2√10=
= 15 +10√10
общий множитель:
= 5(3+2√10)
4) (2√5 +1 )(2√5 - 1) = (2√5)² - 1² = 4*5 -1 = 20-1=19
5) (1+3√5)² = 1² + 2*1 *3√5 + (3√5)² = 1 + 6√5 + 9*5=
=46 +6√5
общий множитель:
= 2(23+3√5)